2013
DOI: 10.1063/1.4803459
|View full text |Cite
|
Sign up to set email alerts
|

InAs/GaAs quantum dot solar cell with an AlAs cap layer

Abstract: We report the effects of the deposition of an AlAs cap layer (CL) over InAs quantum dots (QDs) on the performance of QD solar cells (QDSCs). The growth of AlAs CL over InAs QDs led to the elimination of the wetting layer absorption and hence the enhancement of the open-current voltage, Voc, of a 20-layer InAs/GaAs QDSC from 0.69 V to 0.79 V. Despite a slight reduction in short-circuit current, Jsc, for the QDSC with AlAs CL, the enhancement of the Voc is enough to ensure that its efficiency is higher than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 22 publications
0
45
2
Order By: Relevance
“…This can be explained by the emissions related to excited state transitions observed at shorter wavelengths alongside the ground state emission [19]. In contrast to our previous study [9], the formation of WLs by applying AlAs CLs on QDs during the MBE growth [8].…”
Section: Optical Characteristicscontrasting
confidence: 50%
See 2 more Smart Citations
“…This can be explained by the emissions related to excited state transitions observed at shorter wavelengths alongside the ground state emission [19]. In contrast to our previous study [9], the formation of WLs by applying AlAs CLs on QDs during the MBE growth [8].…”
Section: Optical Characteristicscontrasting
confidence: 50%
“…This thermal process leads to suppression of the second-photon absorption, and hence a lower open-circuit voltage (VOC) [6], [7]. Tutu et al have demonstrated suppression of thermal escape of electrons in QDs by removing the WL [8]. Lam et al have also reported reduction of thermal coupling of QD states from the WL by introducing a potential barrier between the QDs and WL via Si doping [9].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Changing the sizes of QDs and, hence, the position of confined carrier energy levels can easily alter the optical properties of QDbased devices. When QDs are used in a multi-junction SC, the current due to photon absorption by QDs can be tuned to achieve the current-match condition leading to an increase in the power conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we report the saturation of strain-induced dislocations and QD state filling by Si-doping QDs in InAs/GaAs QDSCs with AlAs CLs. Previously, we demonstrated that the deposition of AlAs CLs on InAs QDs could suppress the formation of the WL 8 . Consequently, the effective bandgap of the QDSC was increased, which in turn led to the increase in the thermal activation energy and the V OC .…”
mentioning
confidence: 99%